Antibacterial potentiality of antiulcer and antispasmodic drugs with selected antibiotics against methicillin resistant Staphylococcus aureus: In vitro and in silico studies (Bangladesh Journal of Pharmacology, 2015)
In the present study, the antispasmodic drug mebeverine hydrochloride and the antiulcer drug troxipide were tested for their possible antibacterial properties in vitro. The antimicrobial assays of the above drugs were determined with ampicillin, penicillin and ciprofloxacin against sensitive and resistant strains and their resistance were confirmed through Polymerase Chain Reaction by identifying the presence of the mecA gene. A computer-aided method was used for screening the effectiveness of the drug interactions. Mebeverine and  troxipide inhibited most of the sensitive and resistant strains tested in vitro from 32.5 to 125 µg/mL. The loss of structural alterations of the cell wall was analyzed by atomic force microscopy. In docking studies, troxipide and mebeverine were found to have substantial inhibition against penicillin binding protein 2a (IVQQ) and UDP-N-acetylglucosamine 1-carboxyvinyltransferase (2YVW) receptor proteins that seem to have interacted with most of the residues.Video Clips of Methodology:Set up                2 min 27 secBroth and drug     4 min 40 secInoculation          2 min 29 secIncubation and result     46 sec